2021
DOI: 10.3390/biomedicines9050535
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 Receptors Are Necessary for the Stimulation of NLRP3 Inflammasome and IL-1β Synthesis in Neutrophil-Dominant Asthmatic Airway Inflammation

Abstract: The stimulation of the NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome and IL-1β synthesis are associated with chronic respiratory diseases such as neutrophil-dominant severe asthma. Leukotriene B4 (LTB4) is a principal chemoattractant molecule for neutrophil recruitment, and its receptors BLT1 and BLT2 have been suggested to contribute to neutrophil-dominant asthmatic airway inflammation. However, the relationship between BLT1/2 and NLRP3 in neutrophil-dominant asthmatic airway inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Since previous studies suggested a mediating role of BLT2 in neutrophilic airway inflammation [ 29 , 30 , 31 ], we investigated whether BLT2 had any role in the production of G-CSF. Lung inflammation and mucus secretion were markedly suppressed by treatment with the BLT2 antagonist, LY255283 ( Figure 3 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since previous studies suggested a mediating role of BLT2 in neutrophilic airway inflammation [ 29 , 30 , 31 ], we investigated whether BLT2 had any role in the production of G-CSF. Lung inflammation and mucus secretion were markedly suppressed by treatment with the BLT2 antagonist, LY255283 ( Figure 3 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…NLRP3 inflammasome-dependent IL-1β production also acts as a major chemoattractant of neutrophils and contributes to the development of neutrophilic airway inflammation [ 43 , 47 ]. We previously reported the mediating roles of BLT2 in regulating the production of IL-17 and NLRP3-dependent IL-1β in neutrophilic airway inflammation [ 29 , 30 , 31 ]. Thus, we were curious about the signaling network linking BLT2-mediated G-CSF production to IL-17 or IL-1β production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, in the absence of LTB 4 , sentinel leukocytes will not undergo autocrine signaling via LTB 4 -BLT1. Because LTB 4 -BLT1 engagement activates antimicrobial programs in leukocytes (29,30,45,(57)(58)(59), the absence of autocrine signaling diminishes the ability of sentinel leukocytes directly interacting with Y. pestis to mount an effective antimicrobial response to kill the bacteria. LTB 4 synthesis is also regulated by BLT1 signaling, and autocrine signaling is required to amplify the production of LTB 4 needed to rapidly recruit additional tissue-resident immune cells to the site of infection (29,30,58,60,61).…”
Section: Discussionmentioning
confidence: 99%
“…Its receptors BLT1 and BLT2 have been thought to contribute to the production of airway inflammation in neutrophil‐dominated asthma. Kwak et al 43 established a neutrophil airway inflammation model by attacking mice with house dust mite. It was found that blocking BLT1 or BLT2 could significantly inhibit the activation of NLRP3 inflammasome and the synthesis of IL‐1 β.…”
Section: Nlrp3 and Asthmamentioning
confidence: 99%